Demographic pattern and histopathological profile of neuroendocrine neoplasms diagnosed at a tertiary care center in North East India - Bifica Sofia Lyngdoh; Vandana Raphael; Khonglah, Yookarin; Mishra, Jaya; Marbaniang, Evarisalin; Dey, Biswajit (Asian Journal of Medical Sciences, 2024)
Background: Neuroendocrine tumors (NENs) are a group heterogenous group of tumors that can arise in any organ in the body and have a wide range of aggressiveness. Aims and Objective: To compare the frequency of NENs in our setup to those reported in the literature to age, site, and degree of differentiation by doing a retrospective study. Materials and Methods: Cases of NENs that were diagnosed in the Department of Pathology, in our hospital over the past 5 years were studied considering the age, location, and degree of differentiation. A fresh panel of immunohistochemistry (IHC) was conducted for those cases where IHC was not done. Results: A total of 46 cases of NENs were reviewed. About 56.5% (26 cases) were males and 43.5% (20 cases) were females, with a median age of 46 years. In our study, most of the tumors are found in the gastro-entero-pancreatico-hepatobilliary group followed by the NENs of the endocrine gland (21.7%) and broncho-pulmonary group (15.2%). NENs were graded based on mitotic count and/or Ki-67 labeling index, and/or the presence of necrosis. In total 21 cases (45.7%) had G1 grading, 7 cases (15.2%) had G2 grading, 2 cases (4.3%) had a G3 grading, and 16 cases (34.7%) were graded as neuroendocrine carcinoma. Conclusion: As the majority of the studies do not include benign NENs and those arising from the endocrine glands, therefore comparison of our results can be difficult. This is the first attempt to study the NENs from North East India and to analyze their clinicopathological features.